Conceptualization and measurement of homosexuality in sex surveys: a critical review - Stuart Michaels; Brigitte Lhomond
This article reviews major national population sex surveys that have asked questions about homosexuality focusing on conceptual and methodological issues, including the definitions of sex, the measured aspects of homosexuality, sampling and interviewing technique, and questionnaire design. Reported rates of major measures of same-sex attraction, behavior, partners, and sexual identity from surveys are also presented and compared. The study of homosexuality in surveys has been shaped by the research traditions and questions ranging from sexology to the epidemiology of HIV/AIDS. Sexual behavior has been a central topic at least since Kinsey. Issues of sexual attraction and/or orientation and sexual identity have emerged more recently. Differences in the treatment of men and women in the design and analysis of surveys as well as in the reported rates in different surveys, in different countries and time periods are also presented and discussed. We point out the importance of the consideration of both methodological and social change issues in assessing such differences.